Financial Literacy and Self-employment - Aida Ćumurović; Walter Hyll (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
In this paper, we study the relationship between financial literacy and self-employment. We use established financial knowledge-based questions to measure financial literacy levels. The analysis shows a highly significant correlation between self-employment and financial literacy scores. To investigate the impact of financial literacy on being self-employed, we apply instrumental variable techniques based on information on economic education before entering the labour market and education of parents. Our results reveal that financial literacy positively affects the probability of being self-employed. As financial literacy is acquirable, findings suggest that entrepreneurial activities may be raised via enhancing financial knowledge.
urn:nbn:de:gbv:3:2-53382
Keywords: A20; D03; J23; J24; 330; financial literacy; financial sophistication; self-employment